Intelligent Traffic Signal Control System Based on Edge Computing and Big Data. Issue 3 (October 2020) - Yang, Jinyan; Suo, Hui
Abstract: The traffic in big cities is becoming increasingly congested. Traffic jams need to be solved urgently. Intelligent transportation is the trend of future development. This paper proposes an intelligent traffic light control system based on edge computing and big data. Firstly, a large number of edge computing nodes are used to obtain all kinds of traffic related real-time data; secondly, big data is used to achieve the effective storage and processing of massive data; finally, neural network is used to integrate all the influencing factors to achieve the optimal control of signal lights. Experimental results show that the method is effective.